Environmental and Economic Impacts of Pesticide Use in Intensive Agricultural System: A Case Study in Parongpong District, West Bandung Regency - Pipit, Ayu; Martono, Dwi Nowo; Utomo, Suyud Warno (Jurnal Perlindungan Tanaman Indonesia, 2025)
The intensive use of pesticides in agriculture has raised concerns regarding environmental quality and economic sustainability, particularly in Parongpong District, West Bandung Regency. This study aimed to analyze the impact of pesticide use on soil and water quality as well as its economic implicates on farmers. A mixed-method approach was applied through soil and surface water sampling, laboratory analysis, and structured questionnaires with 100 farmers. Soil quality tests revealed low pH, reduced organic carbon (1.61%), and high cadmium (5.2 mg/kg), indicating soil degradation. Water samples from the Cibeureum River showed that BOD (93.5 mg/L), COD (302 mg/L), and total phosphorus (0.475 mg/L) exceeded national standards, suggesting nutrient overload and pollution linked to pesticide runoff. Economically, although 98% of farmers perceived pesticides as beneficial, the Benefit-Cost Ratio (BCR) analysis resulted in a value of 0.57, implying financial inefficiency. This indicated that the cost of pesticides and mitigation outweighs the actual benefits received from increased crop yields. The gap between farmers’ perception and objective economic and environmental data highlights the need for sustainable solutions. Organic farming practices introduced by local farmer groups, such as Semai Organik and Farm Organic Parongpong, offer promising alternatives for improving productivity while preserving environmental integrity. Promoting environmentally friendly farming methods is essential to ensure long-term ecological balance and economic resilience in the agricultural sector.